2021
DOI: 10.1002/acn3.51403
|View full text |Cite
|
Sign up to set email alerts
|

Zonisamide‐responsive myoclonus in SEMA6B‐associated progressive myoclonic epilepsy

Abstract: We present a female patient in her early twenties with global development delay, progressive ataxia, epilepsy, and myoclonus caused by a stop mutation in the SEMA6B gene. Truncating DNA variants located in the last exon of SEMA6B have recently been identified as a cause of autosomal dominant progressive myoclonus epilepsy. In many cases, myoclonus in the context of progressive myoclonic epilepsy is refractory to medical treatment. In the present case, treatment with zonisamide caused clinical improvement, part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…The author suggested that the gene was dominant-negative or had gain-of-function effects rather than showing haploid deficiency. Upon searching for reported cases of SEMA6B variants, we found seven other variants reported in the literature ( 6 8 , 13 15 ). All of the variants are summarized in Table 1 and Figure 3 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The author suggested that the gene was dominant-negative or had gain-of-function effects rather than showing haploid deficiency. Upon searching for reported cases of SEMA6B variants, we found seven other variants reported in the literature ( 6 8 , 13 15 ). All of the variants are summarized in Table 1 and Figure 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Clonazepam is useful but often leads to considerable sedation and increasing tolerance. Due to the partial response to clonazepam and the short-term improvement after treatment with valproic acid and levetiracetam, myoclonus tends to persist after treatment ( 8 ). Some newer ASMs are reportedly effective, such as piracetam ( 17 ), topiramate ( 18 ), zonisamide ( 19 ), clobazam ( 20 ), and perampanel ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With 14 variants, of which 11 are novel, added to those already reported in the literature, (10)(11)(12)(13)(14)(15) our study leads to a total of 22 heterozygous variants currently identified in SEMA6B in 28 unrelated patients. In all patients for whom DNA of the two parents was available (22/28), these variants had occurred de novo.…”
Section: Discussionmentioning
confidence: 90%
“…Until now, SEMA6B variants have been identified in individuals with epilepsy, including (1) 10 truncating variants in the last exon of SEMA6B in 10 patients with progressive myoclonic epilepsy (PME, MIM #618876), (10)(11)(12)(13)(14) and in one individual with global developmental delay and recurrent febrile seizures, (15) and ( 2) one missense variant in exon 14 in an individual with epilepsy without intellectual disability (Supplementary Table 1). ( 13) Here, we broaden the phenotypic spectrum and the role of SEMA6B by reporting 14 heterozygous variants, of which 11 are novel, identified in 16 unrelated patients with moderate to severe intellectual disability, as well as variable neurological features and seizures in some cases.…”
Section: Introductionmentioning
confidence: 99%